MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN SCIENCE V-LAB PADA MATERI LAPISAN PERMUKAAN BUMI TERHADAP LITERASI SAINS SISWA SMP - Rachman, Lucky Juniar; Indrawati, Indrawati; Rusdianto, Rusdianto (JURNAL PEMBELAJARAN FISIKA, 2023)
ABSTRACT Scientific literacy skills are students' ability to draw conclusions based on scientific knowledge and communicate them orally or in writing. However, in reality the scientific literacy skills of students in Indonesia are still relatively low, therefore a learning model is needed that can improve students' scientific literacy skills, for example by using a guided inquiry learning model. This research aims to test the guided inquiry learning model assisted by science v-lab media on earth's surface layer material which can have an effect on increasing scientific literacy in junior high school students. This research is a quasi-experimental type with a post-test only control design located at SMPN 2 Panti Jember for grade 7 students. The results of the research are that the highest score in the experimental class is 91.66 with an average of 85.05, while the highest score is in the control class. namely 83.3 with an average of 66.40. So it can be said that the use of the guided inquiry learning model assisted by v-lab science media in learning material on the layers of the earth's surface has a significant effect on the scientific literacy abilities of junior high school students.